FEMININE DEATH AS SACRIFICE IN THE LITTLE MATCH GIRL, DEAD MEN’S PATH, AND THE STORY OF AN HOUR - Saputra, Wanda Andres; Karimah, Asmanadia Izzatul; Haliza, Alya Nur; Fitriani, Dinda Ayu; Isyfiani, Tera Sella; Rizal, Muhammad (Lire Journal (Journal of Linguistics and Literature), 2023)
This research article discusses feminine death in three short stories: The Little Match Girl (1906) by Hans Christian Andersen, Dead Men's Path (1972) by Chinua Achebe, and The Story of an Hour (1969) by Kate Chopin. It aims to reveal the existence of extremity and sacrifice in the death of a woman. This study used a qualitative-descriptive design to reveal and investigate the phenomena and forms, or modes, of women's deaths. The theory of feminine death from Elizabeth Bronfen (2017) is used to reveal the extremity and sacrifice of a woman, and the theory of philosophical death and female finitude from Linnell Secomb (1999) is used to reveal the mode and symbols of feminine death. Based on Spradley's theory and analysis, we argue that the three short stories all have extremity and sacrifice; in the short story by Hans Christian Andersen, there is a mode or form of death called "being-towards-death." Furthermore, in the work of Chinua Achebe, there is a mode of death called "the master-slave battle to the death." Lastly, Kate Chopin produced "dwelling-with-death". The three short stories can be found in extremity, sacrificing, and feminine modes of death. Thus, the identification can reveal the feminine death phenomenon in the short story.